Identification and characterization of the inhibitory effect of ART on colorectal cancer cells using Raman spectroscopy. (10th January 2022) - Chai, Senmao; Sun, Xiaodong; Fu, Chuhua; Xu, Qianqian; Ren, Zijing; Xie, Lixia; Ge, Jingjing; Sang, Ming
Abstract: Raman spectroscopy (RS) has been used in clinical diagnostics, tissue engineering, and toxicology experiments owing to its label‐free, low‐destructive, high sensitivity, and strong specificity. Nonetheless, their application has been limited because of the integrated analysis of biological experimental methods and RS. In this study, it was challenged that applied RS in combination with biological experiments to distinguish colorectal cancer (CC) cells from which treated with artesunate (ART), which has obvious antitumor effects. Heavy water (D2 O) was used to detect changes in colorectal cancer cell metabolism. The Raman spectral intensity of the C–D band at 2100–2300 cm −1 was significantly weakened in CC (SW480, SW620, and HCT116) treated with ART. According to the CCK‐8, wound healing, and Transwell assays, the activity of SW480 and SW620 cells was significantly inhibited by ART. Through literature tracking and transcriptome sequencing, multiple signal pathways of SW480 and SW620 cells have changed significantly after treatment with ART, such as "apoptotic signaling pathway, " "cell cycle phase transition, " "mitochondrial part, " and "mRNA metabolic process." The Raman peak area significantly decreased at 490 cm −1, 746 cm −1, 1126 cm −1, 1311 cm −1, 1337 cm −1, and 1582 cm −1 in SW480 and SW620 cells treated with ART. It showed that these Raman bands are associated with ART‐induced apoptosis‐related signaling pathways. In addition, we found that application of the RS in cell type identification will be prosperous. By integrating RS with biological mechanisms, its application in the biomedical field is increasing, and its significance in biological sample detection has become more prominent. Abstract : SW480 and SW620 cells signal pathways ("apoptotic signaling pathway, " "cell cycle phase transition, " "mitochondrial part, " and "mRNA metabolic process") have changed significantly after treatment with ART. The Raman peak area significantly decreased at 490 cm −1, 746 cm −1, 1126 cm −1, 1311 cm −1, 1337 cm −1, and 1582 cm −1 in SW480 and SW620 cells treated with ART. It showed that these Raman bands are associated with ART‐induced apoptosis‐related signaling pathways.